14. ASSESSMENT OF TREATMENT RESULTS FRACTURE OF THE INTERTROCHANTER OF THE FEMUR IN PEOPLE OVER 65 YEARS OLD WITH PFNA NAILS AT SAI GON ITO HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Introduction: Fractures of the intertrochanter are severe fractures, common in the elderly. For most people, the most common difficulties are rehabilitation problems, pressure ulcers, pneumonia caused by lying down for a long time. The PFNA system was introduced by AO/ASIF in 2004. The characteristic design of this ostomy device is to use a neck screw with a large contact area, which helps to compress the cancellous bone, this makes the means of combining bones stronger for the elderly with osteoporosis. At the ITO Hospital in Ho Chi Minh City, PFNA has been performed to combine the intertrochanteric fractures with PFNA, showing many advantages of this method. Therefore, we chose the topic: “Evaluation of the results of treatment of intertrochanter fracture of the femur with PFNA”.Objective: Evaluate hip anatomical recovery, bone healing and hip rehabilitation.Methods: prospective study of 36 patients (11 males, 35 females) with fractures of the intertrochanter, grouped A1, A2, A3 according AO classification, Surgery with PFNA has been used.Results: After 6 months, the bone healing rate is 100%; patients walking normally without pain accounted for 38.9%; can walk, pain on exertion accounts for 50%; Harris scores very well, 38.9%, good 47.2%, average 13.9%.Conclusion: Treatment of intertrochanter fractures with PFNA nails has a very good and effective healing result according to Harris and is good in over 85% of cases, the surgical method is safe.
Keywords: Fracture of the intertrochanter of the femur, PFNA nail.